Habitat value of subsea wells and pipelines for fishery target species in Australia - McLean, Dianne; Speed, Conrad W.; Birt, Matthew Jon; Colquhoun, Jamie; Case, Mark; Stowar, Marcus; Bond, Todd; Ierodiaconou, Daniel; Whitmarsh, Sasha K.; Taylor, Michael D.; Wines, Sam; Booth, David John; et al. (Frontiers in Marine Science, 2022)
Subsea pipelines and wells installed to support the oil and gas industry represent some of the most extensive and numerous anthropogenic structures throughout global marine ecosystems. There remains a paucity of information on the habitat value of these structures for fishery target species and, as a result, little understanding of how decommissioning should be conducted to minimise impacts to populations of these economically and socially important species. We assess the diversity and abundance of species that are targets of recreational and commercial fisheries on 33 subsea wells and 17 pipelines across the tropical north-west and temperate south-east marine regions of Australia. We examine relationships between fish identity and abundance and a range of environmental (e.g. depth, location), infrastructure-specific (e.g. pipeline position, diameter, age, length of pipeline, height of well, position on well) and biological (% cover of epibiota) variables using video filmed by remotely operated vehicles during their routine offshore inspection and maintenance campaigns. A total of 100 fishery target species were observed across subsea well and pipeline infrastructure, 56 species uniquely observed on pipelines and nine unique to wells. The families Lutjanidae (snapper), Serranidae (rock cods, groupers, perch) and Carangidae (trevallies) were most common and abundant on both wells and pipelines. In the north-west, lutjanids were most abundant around the base of wells, in shallow depths, on shorter wells, and where pipelines spanned the seafloor. A greater number of fishery target species and abundance of ocean perch (Helicolenus spp.) were also associated with pipelines that spanned the seafloor in temperate south-east Australia. The combined biomass of three species of snapper on wells in the north-west was 1270 kg, with production levels for these species 16.2 g m2 yr-1 per well. The present study serves as an important reference point for informing decommissioning decisions for pipeline and well infrastructure and demonstrates the utility of industry-held data for science. We suggest that key predictor variables identified here be incorporated into comprehensive before-after-control-impact scientific studies for specific fields/assets to enable prediction of potential impacts of decommissioning scenarios on marine communities present, and quantification of such impacts after the decommissioning activity has occurred.